(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Melastoma malabathricum Linn. commonly known as ‘senduduk’ in Malaysia, belongs to Melastomataceae family. The study was carried out to screen the phytochemicals present in methanol extract of leaf, flower, fruit, and stem and to evaluate the antioxidant activity, total flavonoid and total phenolic contents of these different parts. Phytochemical screening showed that all parts of this plant contained tannins, steroids, phenols and flavonoids. The flower extract was found to have highest total phenolic whereas the leaf demonstrated the highest flavonoid content followed by flower. The results of antioxidant activity from the DPPH assay showed that the flower has the highest radical scavenging activity comparable to quercetin standard while stem showed the lowest activity. The higher content of total phenolics, flavonoids and antioxidant capacity of flower suggests the possibility of its incorporation and exclusion of stem in M. malabathricum preparations for development of newer effective drugs.